‘A Rose for Emily’: The Dichotomy of a Rose - Schweizer, Justine (Université d'Ottawa | University of Ottawa, 2018)
As one of the most prominent figures of Southern literature, William Faulkner is known for his highly accurate and critical depictions of the South, most notably during its transition from the plantation era to the industrial age. His work presents all aspects of the changing South and its colourful cast of characters. Perhaps none are as emblematic and ambiguous as that of "A Rose for Emily"‘s eponymous character, Emily Grierson. Through his innovative use of narration and his portrayal of her, Faulkner represents the transitioning South as it moves from one era to the next, with all the crises and complexities it entails. Written in the prime of the feminist movement, "A Rose for Emily" portrays a character caught between identities: the masculine and the feminine, the past and the present, the passive and the active. Going from subject to object and back again throughout the narrative, Miss Emily Grierson is the embodiment of the rose her creator symbolically gifts her. She is the petals of the flower, supple and soft, and the thorns of the stem, harsh and unyielding.
Keywords: William Faulkner; plantation; industrial age; South